1987
DOI: 10.1080/01635588709513917
|View full text |Cite
|
Sign up to set email alerts
|

α‐Ecdysone, a new bracken fern factor responsible for neoplasm induction in the Egyptian toad (Bufo regularis)

Abstract: Neoplastic lesions were induced in 10 out of 58 experimental toads (Bufo regularis) force-fed with alpha-ecdysone, which naturally occurs in the leaves of bracken fern (Pteris aquilina). The results of this study prove that alpha-ecdysone may be one of the factors responsible for the carcinogenicity of bracken fern plant fed to cattle and other experimental animals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

1988
1988
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 21 publications
1
9
0
Order By: Relevance
“…This author obtained the same result (a carcinogenic effect) in the parasites, O. sudafricana, by injecting its host, B. regularis, with (3-ecdysone [6] as well as gibbcrellin A3 [8]. El-Mofty et al [13] found that feeding the toads B. regularis with a-eedysone induced neo plastic lesions in out of 58 toads. Pamukcu [19] has shown that a low level of bracken fern (P. aquilina) in the ration over a period of a few months may produce bladder tumours in cattle.…”
Section: Resultssupporting
confidence: 55%
See 1 more Smart Citation
“…This author obtained the same result (a carcinogenic effect) in the parasites, O. sudafricana, by injecting its host, B. regularis, with (3-ecdysone [6] as well as gibbcrellin A3 [8]. El-Mofty et al [13] found that feeding the toads B. regularis with a-eedysone induced neo plastic lesions in out of 58 toads. Pamukcu [19] has shown that a low level of bracken fern (P. aquilina) in the ration over a period of a few months may produce bladder tumours in cattle.…”
Section: Resultssupporting
confidence: 55%
“…Mul berry leaves are rich sources of ecdysones [14], Mul berry leaves are edible in some Arab countries. In Egypt, these leaves are used to make rice rolls which are eaten by the natives [6], The results of El-Mofty et al [13] and the present work show that both a-ecdysone and gibberellic acid (gibberellin A3) may be con sidered as carcinogenic substances at least in the Egyptian toad B. regularis. Since ecdysones [14,15] and gibberellic acids [5] are found in some plants that are eaten by man or by cattle, the present work may clarify some points in the field of carcinogenesis.…”
Section: Resultsmentioning
confidence: 79%
“…The models have in cluded Xenopus laevis [4][5][6], Rana pipiens [7,8] and Bufo regularis [9,10], Some investigators have shown that toads can be used as a model to study the development of carcinogens [11], cocarcinogens [12] and vitamins [13], In the majority of these studies, the diagnosis of the induced tumors was based essentially on light microscopy.…”
Section: Introductionmentioning
confidence: 99%
“…Also, El-Mofti [52,53] reported that ecdysone was able to induce neoplastic lesions in toads and mice, a result which appears somewhat surprising when considering the very low doses of ecdysone used. The phytoecdysteroids cyasterone, polypodine B, and decumbesterone A showed potent antitumor activities in a mouse-skin model in vivo in a two-stage carcinogenesis trial, using 7,12-dimethylbenz[a]anthracene as initiator and 12-O-tetradecanoylphorbol-13-acetate (TPA) as promoter [54].…”
Section: Antitumor Activitymentioning
confidence: 99%